DISCRIMINATIVE MODEL OF CERTAIN MOTOR INDICATORS OF FOOTBALL PLAYERS AS SELECTION CRITERIA FOR TEAM POSITION - Goran Vučković; Raša Dimitrijević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Well-designed and implemented selection is one of the important prerequisites for achieving the expected results in the modern competitive sport at all levels. The aim of this work was to determine how the selection was made for Serbian League players, on the basis of their certain motor parameters and the positions in the team. A sample of 25 senior players of a football team competing in the Serbian League is divided into four sub-samples, based on team positions. For assessment of motor characteristics following tests were used: long jump (LJ), Abalac test (AT); 10 seconds push-ups (PU), 30 seconds trunk bends (TB), 20 meter flying start running (20FSR), 20 meter high start running (20HSR), 50 meter high start running (50HSR) and Cooper test (CT) . Based on the obtained results it can be concluded that there are significant differences for variable 20FSR and variable CT (F = 3754, 9835, p = .027, .000, respectively). Three canonical discriminant functions were singled out, where the first explained even 84.6%, the second 14.5% and the third only 1% of the total variance, or in summary first two functions explained 99.0% of the variance. It can be concluded that the selected players, in terms of the position in the team, distinguished first by performing on the Cooper test, followed by the result of 20 meter flying start running, 20 meter high start running, 50 meter high start running, trunk bends, and finally by Abalac test, push-ups and long jump. Observed as a function of certain motor characteristics, it could be concluded that in the selection of players in terms of the playing position confidence level was 72.0% in general level, with the most reliable for goalkeepers (100%), midfielders (71.4%) and defensive players (70.0%), while the smallest was at strikers (50%).